Isu Kepatuhan Syariah pada Akad Musyarakah Mutanaqishah di Indonesia - Sry Muliyani; Mawaddah Rachman; Eka Dewintara; Rahman Ambo Masse (Institut Agama Islam Negeri Parepare, 2022)
The development of Islamic financial institutions in Indonesia has increased quite a bit from year to year. This is because people's interest in saving is quite high in Islamic financial institutions. Interest-based conventional financial institutions can be compared with products from Islamic financial institutions. For example, cooperation-based sharia banking products with a